HUBUNGAN TINGKAT KECUKUPAN ENERGI DAN PROTEIN DENGAN IMT DAN HEMOGLOBIN PADA PASIEN PENGGUNA NAPZA (Studi di RSJD Sei Bangkong Pontianak Tahun 2015) - Tiurma Sinaga; Siti Fatimah Pradigdo; Ronny Aruben (Jurnal Kesehatan Masyarakat (Undip), 2016)
Drug abuse over the years it's prevalence continues to rise. Results of a survey conducted by BNN (National Narcotics Agency) and Puslitkes (Medical Research Center) in 2008 acquired  prevalence rate reached 1.9% and in 2011 increased by 2.2% or approximately 4 million Indonesian people aged 10 to 60 years as abusers of narcotics. Energy and protein needed to maintain or improve the nutritional status of patients with drug rehabilitation. Optimal nutritional status is needed to accelerate the rehabilitation process. The purpose of this study was to determine the relationship of energy and protein sufficiency level with BMI and Haemoglobin. Type of research is observational with cross sectional design. Analysis of the relations between variables using Shapiro- Wilk  and Spearman Rank test statistic. Most of the age of 30-39 years (53%), high school education / high school (68.9%), less energy sufficiency level category (73.3%), good protein adequacy level category (62.2%), BMI categories normal (68.9%), consuming type of shabu (35.5%) and duration of drug use for 4 years (40%), HB normal (68.9%), and all samples manifold male - male as many as 45 people. The study states There a significant correlation with the level of energy sufficiency BMI values (p = 0.001 r = 0.521) .There was no significant association with BMI protein sufficiency level the value is p = 0.001 There is significant correlation with the level of energy sufficiency level of Hemoglobin values (p = 0.011 r = 0.377). And there is a significant relationship with levels of protein sufficiency level of Hemoglobin values (p = 0.001 r = 0.612) in patients with drug abuse in the RSJD Sei Bangkong. Suggestions for RSJD Sei Bangkong expected to do periodic Hemogoblin examinations and actionable giving Fe mainly in the category of anemia, for making a more varied menu.